2020
DOI: 10.1167/tvst.9.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Three Distinct Retinal Capillary Plexuses Using Optical Coherence Tomography Angiography in Myopic Eyes

Abstract: Characterization of the three distinct retinal capillary plexuses using optical coherence tomography angiography in myopic eyes. Trans Vis Sci Tech. 2020;9(4):8, https://doi.org/10. 1167/tvst.9.4.8 Purpose: To segment and quantify three distinct retinal capillary plexuses using optical coherence tomography angiography (OCTA) in myopic eyes. Methods:We analyzed 96 eyes from 62 subjects with myopia (27.76 ± 7.05 years of age) and evaluated 30 normal eyes from 15 subjects (28.33 ± 3.13 years of age) for contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Axial length changes can result in subtle microstructural retinal changes especially in high myopia. 26 , 82 , 83 Previous studies have shown positive correlation between deep retinal layer perfusion density and axial length. The diurnal amplitudes of the deep parafoveal vessel and perfusion density and axial length were positively correlated, and their variations were in-phase with each other (peaks between 2 PM and 3 PM) in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Axial length changes can result in subtle microstructural retinal changes especially in high myopia. 26 , 82 , 83 Previous studies have shown positive correlation between deep retinal layer perfusion density and axial length. The diurnal amplitudes of the deep parafoveal vessel and perfusion density and axial length were positively correlated, and their variations were in-phase with each other (peaks between 2 PM and 3 PM) in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Lower central retinal artery blood velocities [ 20 , 21 ], a narrowing of the retinal vessel diameter [ 21 ], decreased capillary density [ 5 ], and larger foveal avascular zones [ 22 ] have been described in human myopic eyes with no degeneration. Due to the interrelationship between the neurovascular elements, these vascular changes might in turn compromise vascular and neuronal function, premeditate astrocytic reorganization, and be part of the etiological cascade of events that increases the risk to develop posterior pole complications [ 23 , 24 ]. However, the longitudinal effect of myopia on capillaries, astrocytes, and ganglion cells, and how they relate to each other, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reduction in microvascular density may start from the DVP and develop in both the SVP and DVP. With regard to the reason for reduced microvascular density, some [11] attributed it to microvascular loss, and others attributed it to narrowing and stretching of the retinal vessel caused by axial elongation of the eyeball [21, 24]. Conversely, Zhu et al [11] study revealed that DVP densities in the high and superhigh myopia groups were significantly higher than those in the MM group and controls.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA offers results with high repeatability and reproducibility [9, 10]. Nevertheless, different imaging analysis methods have been used in previous studies, which may also contribute to the discrepancies [11, 12]. Currently, the number of studies assessing the retinal microvasculature of myopic eyes using OCTA is relatively small, and the conclusions are inconsistent [13, 14].…”
Section: Introductionmentioning
confidence: 99%